2023
DOI: 10.1001/jama.2023.2661
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Cost, and Consumer Ratings of Popular Nonvalidated vs Validated Blood Pressure–Measuring Devices Sold Online in 10 Countries

Abstract: This study examines the availability, cost, and consumer ratings of blood pressure–measuring devices relative to validation status across 10 countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Regulatory-cleared devices do not always publish their validation data, and many other devices are sold in the market as a consumer device. Picone et al revealed that among the top 100 best-selling BP devices on a popular online site, 79% of upper arm and 83% of wrist cuff devices have not been validated [ 18 ]. Poor BP data acquired by low performance devices may have negative effects on clinical decision, hypertension management, and patient-physician relationships.…”
Section: Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory-cleared devices do not always publish their validation data, and many other devices are sold in the market as a consumer device. Picone et al revealed that among the top 100 best-selling BP devices on a popular online site, 79% of upper arm and 83% of wrist cuff devices have not been validated [ 18 ]. Poor BP data acquired by low performance devices may have negative effects on clinical decision, hypertension management, and patient-physician relationships.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Accuracy has been the subject of debate [ 16 ]. Lack or paucity of validation studies poses a barrier to widespread use in clinical practice [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%